2006
DOI: 10.1136/tc.2005.015313
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent snus use in Finland in 1981–2003: trend, total sales ban and acquisition

Abstract: The total sales ban did not stop snus use; instead, the increase continued after the ban. Friends who travel to neighbouring countries act as go-betweens reselling snus. Snus is used even by the youngest adolescents, thus contributing to the nicotine dependence process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The study by Huhtala et al [28] reports that the total ban for selling snuff in 1995 in Finland did not end snuff use; on the contrary, the increase in use continued after it. It is legal to import snuff for personal use; usually from Sweden.…”
Section: Discussionmentioning
confidence: 95%
“…The study by Huhtala et al [28] reports that the total ban for selling snuff in 1995 in Finland did not end snuff use; on the contrary, the increase in use continued after it. It is legal to import snuff for personal use; usually from Sweden.…”
Section: Discussionmentioning
confidence: 95%
“…This coincided with a strong increase in use of snus (the most common form of smokeless tobacco in Norway): For girls, the rates tripled (from 2 to 7%), while in boys use increased from 19 to 25% (see figure 1). 11 Increasing use of snus has also been found in Finland,12 Sweden,13 and the US 14. This development should spur more studies of the SES correlates of snus use than the two studies we were able to identify; a Swedish study has shown more snus use among children whose parents have compulsory school only, and also among boys and girls who attended vocational upper secondary schooling 15.…”
Section: Introductionmentioning
confidence: 87%
“…Smokeless tobacco use in adolescence has been infrequently studied, but smokeless tobacco is used in early adolescence, and efforts to ban it in some countries, including Finland, have not restricted its use [11]. Adverse physical health-related consequences of smokeless tobacco use are well understood, but whether it potentially contributes to nicotine dependence is, surprisingly, unknown [12].…”
Section: Introductionmentioning
confidence: 99%